2022
DOI: 10.1111/epi.17330
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution hippocampal diffusion tensor imaging of mesial temporal sclerosis in refractory epilepsy

Abstract: We explore the possibility of using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI) to discern microstructural abnormalities in the hippocampus indicative of mesial temporal sclerosis (MTS) at the subfield level. Methods:We analyzed data from 57 patients with refractory epilepsy who previously underwent 3.0-T magnetic resonance imaging (MRI) including DTI as a standard part of presurgical workup. We collected information about each subject's seizure semiology, conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…This damage would be greatest in the DG, which is postulated to be the most affected structure in MTLE-HS ( 58 ). A recent study reported similar results ( 35 ).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…This damage would be greatest in the DG, which is postulated to be the most affected structure in MTLE-HS ( 58 ). A recent study reported similar results ( 35 ).…”
Section: Discussionsupporting
confidence: 75%
“…On the contrary, in the part of the MST task assessing general recognition memory (i.e., discrimination between studied and novel items), their performance did not differ from controls ( 33 ). The aim of our study was to characterize microstructural abnormalities in each of the hippocampal subfields in these patients ( 35 ) and, for the first time, to determine the relation of these metrics with their mnemonic performance on a behavioral pattern separation task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DTI can also better inform us about radiographic diagnoses such as mesial temporal sclerosis (MTS), the most common cause of TLE [ 18 ]. MTS patients show lower orientation dispersion indices and elevated axial diffusivity in the dentate gyrus on DTI compared to no MTS [ 18 ].…”
Section: Structural Brain Imagingmentioning
confidence: 99%